Media dan Sumber Belajar Pada Pembelajaran Aksara Arab Melayu di Kelas V MIS Ali Imron Medan Sumatera Utara - Mursal Aziz; Wapiatul Khairiah; Elvira Zahratunnisa; Andini Syahfitri (JOURNAL SAINS STUDENT RESEARCH, 2023)
Media and learning resources are important factors in success in achieving learning goals. It is undeniable that limited media and learning resources result in many students not understanding the subject matter, so that learning experiences delays due to the absence of adequate learning media and learning resources. Media and learning resources should have been prepared by the teacher before the learning process. The aim to be achieved in the research is to analyze solutions to problems experienced by teachers and students regarding media and learning resources, so that there are no delays in learning Malay Arabic script so that the learning objectives to be achieved can be achieved well. This research uses qualitative research. The researcher intends to describe the analysis of Malay Arabic script learning in class V of MIS Ali Imron Medan, North Sumatra. The population of this study was 1 teacher and 25 students in class V of MIS Ali Imron Medan. In learning Malay Arabic script, we have not maximized the use of learning media because we do not have free time to create media and learning resources in the form of books are facilitated. Suggestions from researchers regarding this problem are that teachers must create Malay Arabic script learning media in the form of media in audio or visual form and create learning resources in the form of LKPD (Learner Worksheets) from student books and relevant sources.